PENGELUARAN PEMERINTAH DAN PENDAPATAN TERHADAP PEMBANGUNAN PENDIDIKAN DI ACEH - . Zulkifli; . Amri; Muhammad Ikhwan (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2015)
This study aimed to analyze the effect of government spending on education and per-capita income to the development of education in the province of Aceh by using panel data. The literacy rate, enrollment rate of primary and secondary schools were utilised to measure the development of education sector as the dependent variable, while public spending on the education sector and per-capita income were used as the independent variables. This study covers 23 districts/cities in Aceh province over a period of years 2008-2012. Based on the Random Effect Model of panel data analysis, the study documented that the government spending on eduaction and percapita income positively and significantly impacted the literacy rate. However, the government spending on the education sector did not significantly influence the enrollment rate of primary school, junior high school, and senior high school. Although the percapita income have no significant impact to the primary school enrollment rate and junior high school, but it has an effect on the enrollment rate of senior high school. The results of this study imply that in order to promote the development of education in the province, the government should increase the budget allocation of income and expenditure for the education sector